Analysis of the Potential for a Hillside Collapse for a Community in Changhua County, Taiwan - Pei Liu; Tung-Hua Tsai; Szu-Hsien Peng (Advances in Civil Engineering)
To create communities that are resistant to disasters, public disaster prevention and response must be reinforced by promoting disaster prevention and knowledge and technology to ensure an adequate response through public participation. Promoting disaster prevention measures reduces the number of factors in communities that pertain to disasters. Changhua County contains 589 villages, 81 of which are prone to hillsides (including protected forest). In addition to original potential debris flow torrent communities, disaster-resistant communities have been established under the guidance of Soil and Water Conservation Bureau (SWCB), Council of Agriculture in Taiwan; Changhua County Government also plans to establish disaster-resistant communities in other hillside communities. This study proposes an expert questionnaire to determine the potential for a hillside disaster and uses an analytical hierarchy process (AHP) and an analytical network process (ANP) to determine the weights of factors that pertain to potential disasters in hillside communities so that these communities can become resistant to disasters.